The molecular motor F-ATP synthase is targeted by the tumoricidal protein HAMLET - Ho, James (2015)
HAMLET (human alpha-lactalbumin made lethal to tumor cells) interacts with multiple tumor cell compartments, affecting cell morphology, metabolism, proteasome function, chromatin structure and viability. This study investigated if these diverse effects of HAMLET might be caused, in part, by a direct effect on the ATP synthase and a resulting reduction in cellular ATP levels. A dose-dependent reduction in cellular ATP levels was detected in A549 lung carcinoma cells, and by confocal microscopy, co-localization of HAMLET with the nucleotide-binding subunits α (non-catalytic) and β (catalytic) of the energy converting F1F0 ATP synthase was detected. As shown by fluorescence correlation spectroscopy, HAMLET binds to the F1 domain of the F1F0 ATP synthase with a dissociation constant (KD) of 20.5 μM. Increasing concentrations of the tumoricidal protein HAMLET added to the enzymatically active α3β3γ complex of the F-ATP synthase lowered its ATPase activity, demonstrating that HAMLET binding to the F-ATP synthase effects the catalysis of this molecular motor. Single-molecule analysis was applied to study HAMLET–α3β3γ complex interaction. Whereas the α3β3γ complex of the F-ATP synthase rotated in a counterclockwise direction with a mean rotational rate of 3.8 ± 0.7 s−1, no rotation could be observed in the presence of bound HAMLET. Our findings suggest that direct effects of HAMLET on the F-ATP synthase may inhibit ATP-dependent cellular processes.